2021
DOI: 10.1002/jbm.b.34927
|View full text |Cite
|
Sign up to set email alerts
|

Generation of bone grafts using cryopreserved mesenchymal stromal cells and macroporous collagen‐nanohydroxyapatite cryogels

Abstract: Bone tissue engineering strategy involves the 3D scaffolds and appropriate cell types promoting the replacement of the damaged area. In this work, we aimed to develop a fast and reliable clinically relevant protocol for engineering viable bone grafts, using cryopreserved adipose tissue‐derived mesenchymal stromal cells (MSCs) and composite 3D collagen‐nano‐hydroxyapatite (nanoHA) scaffolds. Xeno‐ and DMSO‐free cryopreserved MSCs were perfusion‐seeded into the biomimetic collagen/nanoHA scaffolds manufactured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Natural ECM can act as a porous 3D microenvironment "scaffold", with its multitude of growth factors, effector molecules, enzymes and cellular adhesion motifs influencing cell proliferation, gene expression and intracellular signalling [19][20][21]. Due to the complexity and variability of ECM, however, scaffolds used in tissue engineering are typically more tailored to particular functions, such as promoting cell adhesion or differentiation [22,23]. Regardless of the clinical objective or environment, all biomaterial scaffolds share the following essential properties.…”
Section: Biomaterials In Biomedicinementioning
confidence: 99%
“…Natural ECM can act as a porous 3D microenvironment "scaffold", with its multitude of growth factors, effector molecules, enzymes and cellular adhesion motifs influencing cell proliferation, gene expression and intracellular signalling [19][20][21]. Due to the complexity and variability of ECM, however, scaffolds used in tissue engineering are typically more tailored to particular functions, such as promoting cell adhesion or differentiation [22,23]. Regardless of the clinical objective or environment, all biomaterial scaffolds share the following essential properties.…”
Section: Biomaterials In Biomedicinementioning
confidence: 99%
“…Samples were poured in the plastic Petri dishes (35 mm in diameter; the layer thickness was 2 mm) and frozen at -15 °C for 3 h. The obtained disks were stored in the 70 % aqueous ethanol prior to use. 5 mm diameter disks of blood plasma-based macroporous scaffolds were thoroughly washed 5 times with Hanks solution and then twice with a culture medium and seeded with cells as we described early [9].…”
Section: Methodsmentioning
confidence: 99%
“…Earlier, we demonstrated that encapsulation of MSCs in alginate microspheres led to a cessation of division while retaining the cell ability to differentiation into osteogenic, adipogenic, and chondrogenic lineages [7,8]. In another alginatebased 3D system, namely macroporous sponge-like carriers (scaffolds), MSCs retained their proliferation ability and similar to microspheres were capable to multilineage differentiation in the presence of inductors [9]. In the first system, cells are surrounded by a homogeneous hydrogel, while in the second system, they are situated at the interface between phasesthe solid surface of the pores and the liquid culture medium.…”
Section: Introductionmentioning
confidence: 95%
“…As an alternative, the same polymers can be chemically cross-linked using DVS in alkaline ambient. This cross-linker has been used to form stable polysaccharidic networks [46], as the hydroxyl groups of polysaccharides can react with the two electronic-deficient double bonds of DVS, leading to polymer cross-linking.…”
Section: Polymer Cross-linkingmentioning
confidence: 99%
“…These reagents are used to couple carboxylic groups of one polymer with primary amino groups or Other cross-linking protocols, largely used for the fabrication of cryogel scaffolds suitable for bone or cartilage regeneration, are based on coupling reactions with bifunctional agents, such as glutaraldehyde (GA) and divinyl sulfone (DVS) [15,44,45], reported, respectively, in scheme 2 and 3 of Figure 5. A GA coupling reaction can been used for the cross-linking of polymers bearing nucleophiles, such as primary amino groups of gelatin [15], collagen [46], and chitosan [19]. As an alternative, the same polymers can be chemically cross-linked using DVS in alkaline ambient.…”
Section: Polymer Cross-linkingmentioning
confidence: 99%